2020
DOI: 10.1136/bmjsrh-2019-200512
|View full text |Cite
|
Sign up to set email alerts
|

Copper intrauterine device use and HIV acquisition in women: a systematic review

Abstract: ObjectivesTo review systematically copper intrauterine device (Cu-IUD) use and HIV acquisition in women.MethodsWe searched Pubmed, Embase and the Cochrane Library between database inception and 26 June 2019 for longitudinal studies comparing incident HIV infection among women using an unspecified IUD or Cu-IUD compared with non-hormonal or no contraceptive users, or hormonal contraceptive users. We extracted information from included studies, assessed study quality, and summarised study findings.ResultsFrom 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…For this review, we expanded the previous framework to include criteria for assessing RCTs and to define criteria for an additional higher-quality level of studies that were “informative with few limitations” (online supplementary appendix 2). 8…”
Section: Methodsmentioning
confidence: 99%
“…For this review, we expanded the previous framework to include criteria for assessing RCTs and to define criteria for an additional higher-quality level of studies that were “informative with few limitations” (online supplementary appendix 2). 8…”
Section: Methodsmentioning
confidence: 99%
“…CDC considered several factors and opinions in determining whether to update its guidance. First, CDC used two systematic reviews that were conducted preceding the 2019 WHO consultation: 1) an updated systematic review on hormonal contraception and risk for HIV infection to include new evidence since the last review (7), containing a total of 36 studies, 17 of which met minimum quality criteria defined in the review (8), and 2) a systematic review on copper IUD use and risk for HIV acquisition, containing seven studies, three of which met minimum quality criteria (9). The systematic reviews included primary reports of longitudinal studies (randomized clinical trials or observational studies) identified in PubMed or Embase databases through June 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Among the observational evidence examining the association between progestin-only injectables and risk for HIV acquisition, results were inconsistent across studies and limited by methodologic concerns (8). Limited evidence on other progestin-only contraceptives, combined hormonal contraceptives, and copper IUDs did not suggest increased risk for HIV acquisition, compared with other hormonal or nonhormonal contraceptives or no method (8,9). Animal and laboratory data suggest possible biologic mechanisms for an association between hormonal contraceptive use and increased risk for HIV acquisition, including hormonally mediated changes in the vaginal epithelium and alterations in local and systemic immune responses.…”
Section: Rationale and Evidencementioning
confidence: 99%
“…Twenty-eight years, hundreds of articles and more than half a dozen systematic reviews after the spectre of an association between the use of modern contraception and an increased risk of HIV acquisition was first raised, two systematic reviews1 2 published in this Journal issue may, at last, close the debate. The reviews update the evidence on the association, and include the findings of a randomised controlled trial (RCT), the Evidence for Contraceptive Options and HIV Outcomes (ECHO) trial 3.…”
mentioning
confidence: 99%
“…A storm of correspondence supporting the author’s position followed, much of it vitriolic. The systematic reviews1 2 published in this Journal issue demonstrate that a well-conducted, adequately powered RCT trumps observational studies (although perhaps not passionately held beliefs) – but read the reviews and make up your own mind.…”
mentioning
confidence: 99%